Family, gender, and economic violence: Non-compliance with child support payments in Chile - Yopo-Díaz , Martina (2024)
The payment of child support is one of the main challenges regarding gender equity and economic justice. Recent figures show that 84% of child support payments decreed by the family courts are not paid, and in nine out of ten cases the plaintiffs are women. This article explores the experiences of nonpayment of child support from a gender perspective. For this purpose, 18 semi-structured interviews were conducted with women in the cities of Antofagasta, Santiago de Chile, and Temuco, as part of a study on women’s economic autonomy in Chile. The findings show that non-payment of child support is closely linked to the persistence of the feminization of reproduction and the absence of co-responsibility in child-rearing and childcare. It is also related to a reluctance to request the payment of child support as a strategy to avoid economic dependence, vulnerability to violence, and institutional revictimization. This evidence suggests that non-payment of child support constitutes a form of economic violence and that cultural norms and social dynamics with respect to gender are at the root of tensions over co-responsibility in the reproductive sphere.